2016
DOI: 10.1111/ijd.13449
|View full text |Cite
|
Sign up to set email alerts
|

Use of skin-lightening products among selected urban communities in Accra, Ghana

Abstract: The prevalence of skin bleaching was 50.3% in these communities, which is high considering the adverse effects from the practice. We recommend regulation of products by enforcing the law, more education, and a population prevalence study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 22 publications
(59 reference statements)
7
39
0
Order By: Relevance
“…As in Accra Ghana [ 13 ], pigmentation disorders were the commonest adverse effects in our study. People with types IV to VI (like Malagasy people) are particularly affected by hypopigmentation; however, it is not noticed frequently in very light skinned individuals [ 14 ].…”
Section: Discussionsupporting
confidence: 58%
“…As in Accra Ghana [ 13 ], pigmentation disorders were the commonest adverse effects in our study. People with types IV to VI (like Malagasy people) are particularly affected by hypopigmentation; however, it is not noticed frequently in very light skinned individuals [ 14 ].…”
Section: Discussionsupporting
confidence: 58%
“…It is tenable that urban and semiurban residents in nonwestern cultural contexts have higher exposure to western images of ‘lighter beauty’ and skin bleaching advertisements and products and are more exposed to the Internet as well as social media, activities, and festivities. It has been argued that this phenomenon is related to the high skin bleaching prevalence among urban and semiurban residents who aim at meeting ‘lighter’ standards of beauty and enhancing their perceived appearance at social events . It has also been indicated that rural work such as farming exposes people to ultraviolet radiation with subsequent darkening of skin.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural norms, traditions, and religious ceremonies are additional extrinsic drivers that can influence Hg exposure (particularly to Hg 0 and Hg II ) in certain human populations. Application of Hg-containing skin-lightening creams to achieve desired physical appearances is a common practice in some populations, with prevalence rates as high as 50% in some countries (Dlova et al 2015 ; Gbetoh and Amyot 2016 ; Lartey et al 2017 ). Unregulated products often contain either Hg or calomel, or Hg is intentionally added by the user (Copan et al 2015 ).…”
Section: Domain 2: Global Extrinsic and Individual/molecular-level Inmentioning
confidence: 99%